Assessment of Self Medication in Female University Students of Pharmacy and Medicine-A Prevalence Study (Medical Forum Monthly, 2024)
Objectives: To evaluate the tendency, incidence, relevant awareness, attitude and practice of self-medication in female students of pharmacy and medicine.Background: Self medication is a common trait in those students who are studying medicine, pharmacy or other health sciences. Socio economic features, lifestyle status and awareness about the indications of the medicine are direct factors that affect the practice of self medication. Study Design: Observational Comparative Study.Place and duration of study: The study was conducted in three universities of Karachi, two institutes of pharmacy education and one institute of medical sciences from January 2011 to September 2011.Participants and methods: A self-developed, pre-validated questionnaire containing open-ended and close-ended items was used for data collection. 460 female students (age 20-25) enrolled for study after informed consent and knowledge of the study purpose, filled in the questionnaire anonymously.Results: The study based on 460 student shows that self-medication prevails for the OTC medicines (76.27%) and Prescription Only medicines (51.30%).The use of minerals and vitamins by self medication is 54.5%.The most common reason for self medication shown in 306 count is “previous knowledge of drug use”.Conclusion: The students of medical and pharmacy practice self medication to varying degree for both the OTC and Prescription Only medications. The easy access to medications promotes such practice, where as large expense of proper health care plays a pivotal role. This tendency with peril signifies the role of an effective and well regulated pharmaceutical care system with its essential components.